Apotropaic Means and Methods in the Rules of the Trumpets and Banners (1qm 3-4) - Krause, Andrew R. (Henoch, 2020)
Columns 3-4 of the Qumran War Scroll contain a series of prescriptions for inscriptions on trumpets and banners. These have traditionally been read as entirely metaphorical or literary inventions. However, these lists depict an impetus to materiality similar to certain Second Temple Period inscribed metal and papyrus amulets, and they contain many elements in common with what has often been termed the Qumran apotropaic tradition. We should thus question whether these inscriptions might be depicting the manufacture of apotropaic devices for a more mundane usage. That these inscriptions are highly structured and can be grouped into statements of either praise or divine election, both of which are common apotropaic elements, indicates some apotropaic efficacy for the Ya?ad movement. As with the various Qumran tefillin and mezuzot, we should also question whether these inscriptions would have a performative element that would relate them to prayer or incantation.